1998
DOI: 10.1182/blood.v92.3.756.415k36_756_764
|View full text |Cite
|
Sign up to set email alerts
|

The α-Chemokine Receptor CXCR4 Is Expressed on the Megakaryocytic Lineage From Progenitor to Platelets and Modulates Migration and Adhesion

Abstract: CXCR4 is the receptor for the α-chemokine stromal cell-derived factor 1 (SDF-1) and has been shown to be expressed on a diversity of leukocytes. In this report, the expression of the CXCR4 receptor in cells of megakaryocytic lineage and the role of SDF-1 in megakaryocytopoiesis were investigated. Using flow cytometry in combination with reverse transcriptase-polymerase chain reaction (RT-PCR), we observed that bone marrow CD34+, CD61+ cells, blood platelets, and megakaryocytic leukemia cell lines all expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 35 publications
4
57
0
1
Order By: Relevance
“…Most importantly, these CD34ϩcell-derived megakaryocytes have been reported to be morphologically identical to bone marrow megakaryocytes and to produce platelets in vitro that are indistinguishable from normal platelets (Choi et al, 1995a,b;Cramer et al, 1997). We showed, in agreement with published reports, that CD41ϩ megakaryocytes express surface CD4, CXCR4, and CCR5 (Gewirtz et al, 1992;Kouri et al, 1993;Zauli et al, 1995;Basch et al, 1996;Wang et al, 1998;Kowalska et al, 1999;Lee et al, 1999;Riviere et al, 1999) and may be susceptible to infection by both X4 and R5 HIV-1 strains. In addition, we report for the first time, the presence of the CCR3 chemokine receptor on CD34ϩ-cell-derived megakaryocytes.…”
Section: Discussionsupporting
confidence: 90%
“…Most importantly, these CD34ϩcell-derived megakaryocytes have been reported to be morphologically identical to bone marrow megakaryocytes and to produce platelets in vitro that are indistinguishable from normal platelets (Choi et al, 1995a,b;Cramer et al, 1997). We showed, in agreement with published reports, that CD41ϩ megakaryocytes express surface CD4, CXCR4, and CCR5 (Gewirtz et al, 1992;Kouri et al, 1993;Zauli et al, 1995;Basch et al, 1996;Wang et al, 1998;Kowalska et al, 1999;Lee et al, 1999;Riviere et al, 1999) and may be susceptible to infection by both X4 and R5 HIV-1 strains. In addition, we report for the first time, the presence of the CCR3 chemokine receptor on CD34ϩ-cell-derived megakaryocytes.…”
Section: Discussionsupporting
confidence: 90%
“…CXCR4 is mainly expressed on neutrophils, monocytes, dendritic cells (DC), T and B lymphocytes, thymocytes and CD34+ cells from blood and bone marrow. Thus, it is also expressed on cells of the megakaryocytic lineage from progenitors to platelets (Wang et al ., 1998; Kowalska et al ., 1999; Riviere et al ., 1999; Clemetson et al ., 2000). It was the first chemokine receptor shown to be an human immunodeficiency virus‐1 (HIV‐1) co‐receptor.…”
Section: Platelet Chemokine Receptorsmentioning
confidence: 99%
“…Its receptor, CXCR4, is expressed on many different types of hematopoietic cells including megakaryocytes and CD34 ϩ cells. [23][24][25] The bicyclam AMD3100 is a potent, selective, and reversible antagonist of the CXCR4 chemokine receptor and disrupts the binding of CXCR4 to SDF-1, thereby mobilizing hematopoietic cells into the blood. 26 Studies involving animals and humans have shown that AMD3100 treatment resulted in mobilization of hematopoietic progenitor cells [27][28][29][30][31] and that combining AMD3100 with G-CSF had additive effects.…”
Section: Introductionmentioning
confidence: 99%